2017
DOI: 10.1142/s021830131750046x
|View full text |Cite
|
Sign up to set email alerts
|

Strangeness chemical potential from the baryons relative to the kaons particle ratios

Abstract: From a systematic analysis of the energy-dependence of four antibaryon-to-baryon ratios relative to the antikaon-to-kaon ratio, we propose an alternative approach determining the strange-quark chemical potential (µ s ). It is found that µ s generically genuinely equals one-fifth the baryon chemical potential (µ b ). An additional quantity depending on µ b and the freezeout temperature (T ) should be added in order to assure averaged strangeness conversation. This quantity gives a genuine estimation for the pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…In the HRG model; an ideal gas of point-like hadrons characterized by the Hagedorn mass spectrum which is consisting of a discrete (so-far measured) and a continuous (still missing hadron states), various higher-order thermodynamic quantities have been analyzed 60 . In a previous study 61 , one of the authors (AT) concluded that the missing states are not considerably contributing to the lower-order thermodynamic quantities, especially the first-order ones, the particle number or the particle multiplicity. Thus, the inclusion of missing states would not improve the thermal model capability in reproducing the horn-like structure of the K + /π + ratio.…”
Section: /19mentioning
confidence: 99%
“…In the HRG model; an ideal gas of point-like hadrons characterized by the Hagedorn mass spectrum which is consisting of a discrete (so-far measured) and a continuous (still missing hadron states), various higher-order thermodynamic quantities have been analyzed 60 . In a previous study 61 , one of the authors (AT) concluded that the missing states are not considerably contributing to the lower-order thermodynamic quantities, especially the first-order ones, the particle number or the particle multiplicity. Thus, the inclusion of missing states would not improve the thermal model capability in reproducing the horn-like structure of the K + /π + ratio.…”
Section: /19mentioning
confidence: 99%